Artesunate Protects Against the Organ Injury and Dysfunction Induced by Severe Hemorrhage and Resuscitation. Issue 2 (February 2017) - Sordi, Regina; Nandra, Kiran K.; Chiazza, Fausto; Johnson, Florence L.; Cabrera, Claudia P.; Torrance, Hew D.; Yamada, Noriaki; Patel, Nimesh S. A.; Barnes, Michael R.; Brohi, Karim; Collino, Massimo; Thiemermann, Christoph
Abstract : Objective: To evaluate the effects of artesunate on organ injury and dysfunction associated with hemorrhagic shock (HS) in the rat. Background: HS is still a common cause of death in severely injured patients and is characterized by impairment of organ perfusion, systemic inflammatory response, and multiple organ failure. There is no specific therapy that reduces organ injury/dysfunction. Artesunate exhibits pharmacological actions beyond its antimalarial activity, such as anticancer, antiviral, and anti-inflammatory effects. Methods: Rats were submitted to HS. Mean arterial pressure was reduced to 30 mm Hg for 90 minutes, followed by resuscitation. Rats were randomly treated with artesunate (2.4 or 4.8 mg/kg i.v.) or vehicle upon resuscitation. Four hours later, parameters of organ injury and dysfunction were assessed. Results: Artesunate attenuated the multiple organ injury and dysfunction caused by HS. Pathway analysis of RNA sequencing provided good evidence to support an effect of artesunate on the Akt-survival pathway, leading to downregulation of interleukin-1 receptor-associated kinase 1. Using Western blot analysis, we confirmed that treatment of HS rats with artesunate enhanced the phosphorylation (activation) of Protein kinase B (Akt) and endothelial nitric oxide synthase and the phosphorylation (inhibition) of glycogen synthase kinase-3β (GSK-3β). Moreover, artesunate attenuated the HS-induced activation of nuclear factor kappa B and reduced the expression of proinflammatory proteins (inducible nitric oxide synthase, tumor necrosis factor-α, and interleukin 6). Conclusions: Artesunate attenuated the organ injury/dysfunction associated with HS by a mechanism that involves the activation of the Akt-endothelial nitric oxide synthase survival pathway, and the inhibition of glycogen synthase kinase-3β and nuclear factor kappa B. A phase II clinical trial evaluating the effects of good manufacturing practice-artesunate in patients with trauma and severe hemorrhage is planned. Abstract : Supplemental Digital Content is available in the text